2013
DOI: 10.1371/journal.pone.0080975
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADPH Oxidase Activation in Oligodendrocytes Reduces Cytotoxicity Following Trauma

Abstract: Spinal cord injury is a debilitating neurological disorder that initiates a cascade of cellular events that result in a period of secondary damage that can last for months after the initial trauma. The ensuing outcome of these prolonged cellular perturbations is the induction of neuronal and glial cell death through excitotoxic mechanisms and subsequent free radical production. We have previously shown that astrocytes can directly induce oligodendrocyte death following trauma, but the mechanisms regulating thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…We also observed that other unidentified cells also account for ~20% ROS production at 7 dpi. These unidentified cells may be oligodendrocytes, as activation of NOX has been detected in oligodendrocytes after SCI and inhibition of NOX activity attenuates excitotocicity of oligodendrodytes (Johnstone et al, 2013). However, the most prominent gp91 phox co-localization occurred in macrophage/microglia (TomL-positive cells) at 3 and 7 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that other unidentified cells also account for ~20% ROS production at 7 dpi. These unidentified cells may be oligodendrocytes, as activation of NOX has been detected in oligodendrocytes after SCI and inhibition of NOX activity attenuates excitotocicity of oligodendrodytes (Johnstone et al, 2013). However, the most prominent gp91 phox co-localization occurred in macrophage/microglia (TomL-positive cells) at 3 and 7 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…However, normal communication between astrocytes and oligodendrocytes through CXs is interrupted in pathological conditions, thereby resulting in oligodendrocyte death and subsequent demyelination. Activated astrocytes can also exacerbate oligodendrocyte cell death by reducing extracellular zinc concentrations, which then initiates NADPH oxidase activation within oligodendrocytes through stimulation of Ca 2+ -permeable AMPA receptors (Johnstone et al, 2013). These results show that activated astrocytes exert both positive and negative influences on oligodendrocyte pathophysiology, similar to the dual-faced nature of microglia discussed below.…”
Section: Crosstalk Between Oligodendrocytes and Other White Mattermentioning
confidence: 99%
“…8,9 Therefore, therapeutically targeting oxidative enzymes will prevent axonal demyelination, preserve oligodendrocyte integrity and spare neuronal loss. 10 Zonisamide (1,2-benzisoxazole-3-methanesulfonamide; ZNS) is an antiepileptic drug that has already been approved for clinical use. Several clinical studies have reported the wide clinical spectrum of ZNS against both psychiatric and neurological disorders.…”
Section: Introductionmentioning
confidence: 99%